If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 + x = 40 + 5x Solving 56 + x = 40 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 56 + x + -5x = 40 + 5x + -5x Combine like terms: x + -5x = -4x 56 + -4x = 40 + 5x + -5x Combine like terms: 5x + -5x = 0 56 + -4x = 40 + 0 56 + -4x = 40 Add '-56' to each side of the equation. 56 + -56 + -4x = 40 + -56 Combine like terms: 56 + -56 = 0 0 + -4x = 40 + -56 -4x = 40 + -56 Combine like terms: 40 + -56 = -16 -4x = -16 Divide each side by '-4'. x = 4 Simplifying x = 4
| 5/8x-10=0 | | 8/5x-5= | | 15x-10+10x= | | 12x-4=30x-120 | | T=0.3m^2-5.1m+9 | | 9(3x-4)=26x-3 | | 9(3x-4)=26(x-3) | | 2x+2y-27=0 | | 5x+4+3x-x+7=6x-8 | | X^2+0.11x-0.057=0 | | 13x=12x-1 | | 21x^2+14x-40=0 | | 7+x(7)=3 | | 2x-5yi=4+15i | | 4/16-15/25 | | 15-3t=17-t | | 56+x=5(8+x) | | 7y^2-8=73 | | p-3q=2 | | 3x+8x=3x-5 | | 3p-7=3p+11 | | 4x+4+4x+4x+3=180 | | 4=k+8 | | -3x^2-24x+36=10 | | 3x+y=51 | | 3x^2+3y^2+3z^2-x+6y+3z=9 | | (u-3)(u+4)= | | -3x^2-24x+12=10 | | (2y-7)=(14-2)+4y | | ((5^(-1/2))*(5x^(5/2)))/(5x)^(3/2) | | y=-5/7x | | 1/10x^3-15/2-25 |